プログラム・数学リファレンス

x=-e^(2t)∫3t^2e^(-2t)dt+te^(2t)∫3te^(-2t)dtの解き方

非斉次方程式の特殊解の計算が面倒だったので記事にしました。

\(x=-e^{2t}\int_{}{}3t^2e^{-2t}dt+te^{2t}\int_{}{}3te^{-2t}dt\)を解くのに必要な道具

部分積分

部分積分

$$\int_{}{}f(x)g(x)dx=f(x)G(x)-\int_{}{}f'(x)G(x)dx$$

\(x=-e^{2t}\int_{}{}3t^2e^{-2t}dt+te^{2t}\int_{}{}3te^{-2t}dt\)の解き方

$$x=-e^{2t}\int_{}{}3t^2e^{-2t}dt+te^{2t}\int_{}{}3te^{-2t}dt$$

$$=-e^{2t}\left(-\frac{3}{2}t^2 e^{-2t}+3\int_{}{}t e^{-2t}dt\right)+te^{2t}\left(-\frac{3}{2}te^{-2t}+\frac{3}{2}\int_{}{}e^{-2t}dt\right)$$

$$=-e^{2t}\left(-\frac{3}{2}t^2 e^{-2t}+3\left(-\frac{1}{2}te^{-2t}+\frac{1}{2}\int_{}{}e^{-2t}dt\right) \right)+te^{2t}\left(-\frac{3}{2}te^{-2t}-\frac{3}{4}e^{-2t}\right)$$

$$=-e^{2t}\left(-\frac{3}{2}t^2 e^{-2t}+3\left(-\frac{1}{2}te^{-2t}-\frac{1}{4}e^{-2t}\right) \right)+te^{2t}\left(-\frac{3}{2}te^{-2t}-\frac{3}{4}e^{-2t}\right)$$

$$=-e^{2t}\left(-\frac{3}{2}t^2 e^{-2t}-\frac{3}{2}te^{-2t}-\frac{3}{4}e^{-2t} \right)-\frac{3}{2}t^2-\frac{3}{4}t$$

$$=\frac{3}{2}t^2+\frac{3}{2}t+\frac{3}{4}-\frac{3}{2}t^2-\frac{3}{4}t$$

$$=\frac{3}{4}t+\frac{3}{4}$$

$$=\frac{3}{4}(t+1)$$

参考文献